Does environmental regulation improve public health? Evidence from China's Two Control Zones policy - Yang, Ningze; Liu, Ziwei; Lin, Yuxi; Yang, Yongliang (Frontiers in Public Health, 2023)
The environmental regulation policy can affect public health by reducing the environmental pollution. The Two Control Zones (TCZ) policy is the earliest and stricter environmental regulation in China. Based on the policy experiment of TCZ, this paper analyzes the role of TCZ policy in improving public health using the DID model and data from 112 cities. The study finds that the TCZ policy can significantly improve public health, and this improvement effect was continuous and lagging. When considering city heterogeneity in terms of economic and geographical conditions, the study further found that the impact of improvement is exacerbated for cities in more heavily non-provincial capital and central and western regions, respectively. In addition, the results of mediating test show that TCZ policy improves public health by reducing the environmental pollution. Our research fills the gap in the literature on the micro effects of environmental regulation policy on public health in developing countries. In the Global Health Strategy context, this study attempts to provide policy references for developing countries to improve public health by realizing environmental regulation.